Estratégias de enfrentamento em jogadores de futebol - Verardi, Carlos Eduardo Lopes [UNESP]; Neiva, Cassiano Merussi [UNESP]; Pessôa Filho, Dalton Müller [UNESP]; Nagamine, Kazuo Kawano; Miyazaki, Maria Cristina de Oliveira Santos (My University, 2011)
The aim of this study was to identify scores of interest related to coping strategies used by professional and amateur football players. Participants were 134 male football players, 71 professionals (age=22,77±3,98 years) and 63 amateurs (age=17,18±0,84) from three teams participating on the First Division State Championship). The players answered individually to the Coping with Problems Scale. Significance level was P<0.05. When coping strategies were compared based on game position and player category (professional or amateur), lateral player amateurs used more wishful thinking /religious practices (P=0.042) than professionals. Coping Focused Problem was the most used strategy used by both the professionals and amateurs, except the amateur laterais, who used more wishful thinking /religious practices.

O objetivo deste estudo foi, identificar escores de interesse relativos às estratégias de enfrentamento utilizadas entre jogadores de futebol profissional e amador. Participaram 134 jogadores de futebol do sexo masculino, 71 profissionais (idade=22,77±3,98 anos) e 63 amadores (idade=17,18±0,84 anos) de três equipes que participam dos Campeonatos Estaduais da Primeira Divisão. Os jogadores responderam individualmente a Escala Modos de Enfrentamento de Problema. O nível de significância adotado foi P<0,05. Quando comparadas as estratégias de enfrentamento por categoria e posição de jogo, os laterais amadores utilizaram mais o pensamento fantasioso/práticas religiosas (P=0,042) do que os profissionais. A estratégia focalizada no problema foi a mais utilizada tanto por profissionais como por amadores, exceto pelos laterais amadores, que utilizavam mais pensamento fantasioso/práticas religiosas.
Coping strategies in football players
Keywords: Coping; Football|Game position; Adaptação psicológica; Futebol; Posição de jogo